PERSEPSI WISATAWAN TENTANG DESTINASI WISATA TAMAN MARGA SATWA DAN BUDAYA KINANTAN DI KOTA BUKITTINGGI - Putri, Novia Sri; Chair, Ira Meirina; Waryono, Waryono (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research aimed to describe the perception of tourists about tourist destinations Wildlife Park and Kinantan’s Culture in Bukittinggi terms of indicators attractions, accessibility, amenitas, human resources, image and price. The population is tourists visiting tourist destinations Wildlife Park and Kinantan’s Culture in Bukittinggi numbered 53.853 peoples. Sampling technique using incidental sampling, are 100 peoples. Data was collected using a questionnaire and analyzed through descriptive analysis. The results showed that Perception of tourists about tourist destinations Wildlife Park and Kinantan’s Culture in Bukittinggi in the category quite well (87%). While based on the indicators: 1) Tourist attractions in the category quite well (65%), 2) accessibility in the category quite well (44%), 3) Amenitas in the category quite well (60%), 4) human resources in the category quite well (49%), 5) image in the category quite well (50%), 6) Prices in the category quite well (67%). Keyword: Perception, Tourist Destinations, Tourists.